Social media communication patterns of Artificial Intelligence (AI) in five leading AI tools - Lutfi Adji Ardiansyah; Muhammad Farizan Saputera; Edison Bonartua Hutapea (Privietlab, 2026)
This research is motivated by the development of digital technology, which drives significant changes in the way organizations and products, specifically Artificial Intelligence (AI) tools, communicate with their public. Social media has become a strategic space to build relationships, image, and public trust. The scope of this research is limited to five AI tools (ChatGPT/OpenAI, Gemini/Google, Perplexity, Meta AI, and Microsoft Copilot) and five social media platforms (X/Twitter, Instagram, TikTok, Facebook, and YouTube). The objectives of this research are to determine the distribution of platforms used, the level of activity and content intensity, the digital communication patterns formed, and the position of each AI tool in the communication strategy matrix. The research approach employs a quantitative-descriptive content analysis (Krippendorff, 2018) combined with systematic digital observation over a 14-day period, with two independent coders and Cohen’s κ = 0.782 (substantial agreement). The results show that X/Twitter is the platform with the highest frequency of use. Based on the communication strategy matrix, ChatGPT and Microsoft Copilot are in the quadrant of using many platforms with high content intensity, while Gemini dominates in terms of total content. Another finding shows that a high number of followers is not always directly proportional to the engagement rate, where content quality such as celebrity endorsement (as in Perplexity) is able to generate organic interactions that far exceed its competitors.